Development of Clitoria ternatea as a biopesticide for cotton pest management: assessment of product effect on Helicoverpa spp. and their natural enemies. Issue 2 (10th January 2015) - Mensah, Robert; Leach, David; Young, Alison; Watts, Nick; Glennie, Peter
Abstract The Australian cotton industry is now dominated by transgenic (Bt) varieties, which provide a strong platform for integrated pest management (IPM) of Helicoverpa spp. (Lepidoptera: Noctuidae). New IPM‐compatible tools are required to manage the development of resistance in Helicoverpa spp. and the control of other sucking pests. A 10‐year study commenced in 2001 to identify short‐range, non‐volatile compounds on organ surfaces of plants that deter feeding or oviposition, or are toxic and do not support development of Helicoverpa spp. on cotton plants. The results of the initial study identified Clitoria ternateaL. (Fabaceae) as non‐preferred for Helicoverpa spp. oviposition and larval feeding. The study found that C. ternatea fractionalized extract mixture (fractions 2, 3, 4, and 6) caused oviposition and feeding deterrence as well as direct toxicity to Helicoverpa spp. This study has developed an oil‐based semiochemical product from C. ternatea identified in the initial study into a potential commercial product. The application of 1–2% (vol/vol) of the oil‐based formulation of the C. ternatea mixture against Helicoverpa spp. on commercial transgenic and conventional cotton crops resulted in Helicoverpa spp. oviposition and larval feeding deterrence, as well as caused direct mortality to larvae. No negative effect on beneficial insects was observed. In conclusion, the ability of the oil‐based C. ternatea mixture to control Helicoverpa spp. infestations, while conserving beneficial insect populations, suggests its potential for use in supplementing IPM programs to reduce the use of synthetic insecticides on transgenic and conventional cotton crops.